Characterization of an extracellular β-d-fructofuranosidase produced by Aspergillus niveus during solid-state fermentation (SSF) of cassava husk - Fernandes, Maysa Lima Parente [UNESP]; Jorge, João Atílio; Guimarães, Luis Henrique Souza (Hindawi, 2018)
β-d-Fructofuranosidases are biotechnologically important enzymes produced by various organisms. Here, Aspergillus niveus produced an extracellular β-d-fructofuranosidase during SSF of cassava husk. This enzyme was purified 8.5-fold (recovery of 5.2%). A 37-kDa protein band was observed after 8% SDS-PAGE. Native molecular mass is 91.2 kDa. Optimal temperature and pH of activity were 55°C and 4.5, respectively. The enzyme was stable at 50°C for 1 hr, and 80% of its activity was retained after 1 hr at pH 8.0. The enzymatic activity was improved by Mn2+, was resistant to most solvents, and was inhibited by Triton X-100 and Tween 20. Km and Vmax with sucrose were 22.98 mM and 120.48 U/mg of protein, respectively. With Mn2+, these values were 16.31 mM and 0.30 U/mg of protein. The enzyme did not hydrolyze inulin and for this reason can be considered a true invertase. Thus, A. niveus β-d-fructofuranosidase holds promise for invert sugar production. Practical applications: β-d-Fructofuranosidase is an enzyme that can be applied to different industrial sectors, especially food and beverage industries. It is responsible for the hydrolysis of sucrose and yields an equimolar mixture of D-glucose and D-fructose, named as inverted sugar syrup, with broad applications in the confectionery industry. The Aspergillus niveus enzyme hydrolyzed only sucrose here and can be considered a true invertase, showing its potential for application to invert sugar production. Besides, the use of cassava husk for enzyme production means an interesting utilization route of this agroindustrial residue. Thus, characterization of this enzyme is an important step for identification of its potential for practical applications.
Keywords: agroindustrial residue; Aspergillus niveus; cassava husk; invertase; solid-state fermentation